Human Trafficking and Prostitution in Mozambique: the Mualy, Amalapos and the Police (Global Journal of Human-Social Science, 2019)
This article discusses processes of human trafficking for prostitution in Mozambique It begins by situating the African continent within the dynamics of globalization processes associating human trafficking with poverty and discussing it as a profitable illegal activity conducted on a global scale It continues by presenting the historical factors and economic constraints that put the Mozambican population in a vulnerable situation in relation to human trafficking and prostitution The article then examines how the perceptions of police regarding women trafficked for prostitution are affected by the local institution referred to as Mualy Quantitative data come from the Statistic Brain Research Institute compiled from the following reports UNAIDS World Bank and Demographic Dividend for the period of 2010 to 2017 Qualitative data were collected through ten interviews with the Provincial Command Squads of the Police of the Mozambique Republic PRM of Nampula a city located in northern Mozambique Results show that cultural factors interfere with how Mozambican police perceive human trafficking for prostitution and that such interferences undermine authorities strategies to combat this type of crime
Keywords: human trafficking; prostitution; mualy; amalapo; police